Two Illuminated Text Collections of Namgyal Monastery: A Study of Early Buddhist Art and Literature in Mustang , by Christian Luczanits and Markus Viehbeck - Laurent, Yannick (Indo-Iranian journal, 2022)
"Two Illuminated Text Collections of Namgyal Monastery: A Study of Early Buddhist Art and Literature in Mustang , by Christian Luczanits and Markus Viehbeck" published on 30 Nov 2022 by Brill.